Patterns of stress generation differ depending on internalizing symptoms, alcohol use, and personality traits in early adulthood: a five year longitudinal study. Issue 6 (2nd November 2021) - Goldstein, Brandon L.; Armeli, Stephen; Adams, Rachel L.; Florimon, Martin A.; Hammen, Constance; Tennen, Howard
ABSTRACT: Background: Depression is thought to generate stressful life events. However, other internalizing symptoms such as anxiety or post-traumatic stress and individual difference variables such as personality traits and alcohol use may contribute to stressful life events. Whether stress generation is specific to depression or generalized to these other variables is unclear. Therefore, we tested whether stress generation was depression specific or generalizable to anxiety, PTSD, alcohol use, neuroticism, and extraversion. Design: Two-wave longitudinal study with a five-year follow-up. Methods: 917 young adults completed measures of internalizing symptoms, alcohol use, neuroticism, and extraversion during college and five years later along with an interview-based measure of life events. Results: Symptoms of depression, anxiety, PTSD, and neuroticism exhibited bivariate predictive effects on interpersonal-dependent events. When considering internalizing symptoms in the aggregate, stress generation was specific to symptoms rather than neuroticism. Furthermore, interpersonal-dependent life events mediated Time 1 internalizing symptoms predicting Time 2 symptoms. Conclusion: Our results indicate that stress generation applies to internalizing symptoms broadly rather than specifically to depression. Moreover, neuroticism was no longer a significant predictor of life events when examined with internalizing symptoms simultaneously. These results support the value of integrative models that test numerous factors predicting stressful life events.